Peran dan Tanggung jawab Masyarakat dan Pemerintah Terhadap Pendidikan Islam - M.Yunus Abu Bakar; Siti Nur Maulidiyah Munandari; Zainia Zein (Pusat Riset dan Inovasi Nasional, 2024)
Islamic education plays an important role in shaping the character and morals of individuals and society as a whole. The success of Islamic education does not only depend on educational institutions alone, but also involves the participation and responsibility of the community and government. Society, as the students' closest environment, has an obligation to create an atmosphere that is conducive to the development of Islamic education. This can be realized through active participation in supervising, providing support, and participating in activities related to Islamic education. On the other hand, the government plays a role as a regulator and facilitator in developing Islamic education. The government is responsible for formulating policies, providing infrastructure, and providing adequate budget allocations to ensure optimal implementation of Islamic education. Harmonious collaboration between society and government in carrying out their respective roles and responsibilities will create a strong and sustainable Islamic education ecosystem. This abstract provides a general overview of the roles and responsibilities of society and government in Islamic education. The community plays a role in creating a supportive environment, while the government is responsible for providing regulations and supporting facilities for the optimal implementation of Islamic education